2017
DOI: 10.1002/bit.26234
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic engineering of fatty alcohol production in transgenic hairy roots of Crambe abyssinica

Abstract: Biotechnological production of fatty alcohols, important raw materials in the chemical industry, has been receiving considerable attention in recent years. Fatty alcohols are formed by the reduction of fatty acyl-CoAs or fatty acyl-ACPs catalyzed by a fatty acyl reductase (FAR). In this study, we introduced genes encoding FARs from Arabidopsis thaliana (AtFAR5) and Simmondsia chinensis (ScFAR) into Crambe abyssinica hairy roots via Agrobacterium rhizogenes-mediated transformation. The efficiency of the transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Comparatively, the total lipid classes at 0 days were one-fold higher than those detected at 8 days of ripening in both cultivars and seasons. These fatty alcohols might be formed by reducing fatty acyl-CoAs or fatty acyl-ACPs catalyzed by a fatty acyl reductase [ 16 ]. Rowland et al reported that NADPH-dependent fatty acyl reductases catalyze the development of fatty alcohols from fatty acyl-CoAs or fatty acyl-ACPs [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Comparatively, the total lipid classes at 0 days were one-fold higher than those detected at 8 days of ripening in both cultivars and seasons. These fatty alcohols might be formed by reducing fatty acyl-CoAs or fatty acyl-ACPs catalyzed by a fatty acyl reductase [ 16 ]. Rowland et al reported that NADPH-dependent fatty acyl reductases catalyze the development of fatty alcohols from fatty acyl-CoAs or fatty acyl-ACPs [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Transgenic plants are increasingly becoming an extremely attractive source of desirable biologically-active compounds [25][26][27][28][29][30][31]. The dynamic development of genetic engineering tools now allows plants to be modified for the most efficient production of many therapeutics, such as recombinant proteins or secondary metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Considering these, the aim of this research was to study the metabolic pathway and biosynthetic genes functioning in diosgenin formation. The results could be applied to engineer the metabolic flux toward diosgenin biosynthesis in order to improve the accumulation of diosgenin in either the whole plant or the hairy root cultures of fenugreek, which have been considered as promising alternative platforms as compared to the wild plant . In the present study, the full‐length CDS of 14 genes involved in the diosgenin biosynthesis pathway were identified (Figures S5B–S15C).…”
Section: Discussionmentioning
confidence: 77%